Formação socioespacial do Noroeste do Paraná e a ação da Companhia Colonizadora Byington - Fabrini, Flávio (2014)
This study have like objective to analyze the process of formation social - spatial, through of the action of the Byington Company, in the region of the Northwest of the State of the Paraná, in the micro region of the city of the Umuarama (Paraná - Brazil) and as from 1950, the Company focalized the process of the formation of the space where they are the municipal districts of the Altônia, Esperança Nova, Pérola, São Jorge do Patrocínio and Xambrê. The economic base for the effective occupation and capitalist of this region of the Northwest of the Paraná was the production of the plantation of Coffee tree; it was motive which brought immigrant of the various portions of the country. The history of the coffee planting in the Paraná is formatted in your origin for a slow process of production due, mainly, at the difficulties of the flowing off and at the crisis which affect the product in the scenery general. Posteriorly, different colonists companies provide the necessary infrastructure and they implant a rhythm of the occupation enough intense in this region; they used like discourse the incentive of the production of coffee tree. This was enabled great opportunity of the business to the State to the Companies. The politic adopted for the State of the Paraná contributed for the actions of the private initiative, it is used like a way officially established for this pertaining to or relative to immovable property agents. In the North region and in the area correspondent at the Newest North of the Paraná were several pertaining to or relative to immovable property agents which they received concession of the grounds. So, the activities of the economic coffee tree are related at the process historic of the growing of this region, it has economy the principal characteristic of the occupation of the territory. Therefore, with the landing of the Colonists Companies, the territory passed for a process of the reoccupation, where this enterprisers turned their selves the protagonists of the production of the space, where rested other agents which they be alive in that territory, lay aside of the history process. In that sense, we analyze the peculiarness in the process of the recuperation of that area in the scenery of the Northwest of the Paraná, through of the activities of the CTNP/CMNP, where we present the likeness and search to comprehend the specificity and similitude realized for the Byington Company. In that part, it gained importance urbanistic aspects of the morphology of the small cities which so far as others in the Northwest of the Paraná, was main delineated, showing a nucleus initial projected. We show like occurred the production of that space and your materialization under the sight of the contemporary Geography.